Revision of the Amphibolips ‘niger’ group with the description of a new species (Hymenoptera: Cynipini) - Cuesta-Porta, Victor; Melika, George; Nicholls, James A.; Stone, Graham N.; Equihua-Martinez, Armando; Estrada-Venegas, Edith; Pujade-Villar, Juli (Zootaxa, 2023)
Amphibolips is currently divided into two species-groups, clearly differentiated by adult and gall morphology. The ‘niger’ group of Amphibolips species is revised. This complex includes eight species: A. gumia Kinsey, A. jubatus Kinsey, A. elatus Kinsey, A. maturus Kinsey, A. nebris Kinsey, A. niger Kinsey, A. pistrix Kinsey and A. ufo Cuesta-Porta & Pujade-Villar sp. nov. We provide descriptions of new species and re-descriptions of known species, diagnoses, keys to complexes and species. The possibility of the ‘niger’ complex belonging to a new genus is also discussed.